On characterizing skeletal muscle contraction properties. Experimental and simulation methodology - Sierra, M.; Muñoz, M.J.; Grasa, J. (Jornada de Jóvenes Investigadores del I3A, 2012)
The main objective of this work is to characterize the fatigue contractile properties of threedifferent rat muscles (Tibialis Anterior, Extensor Digitorium Longus and Soleus) in order toobtain experimental parameters for numerical simulations.Experiments were conducted “in vivo" on three groups (n = 6) of male Wistar rats (210 +/- 11g)using a protocol developed by authors in previous works. Muscles were subjected to anelectrical stimulus to achieve tetanic contraction during ten seconds. Digital Image Correlationwas used during tests for 3D strain and displacements measurement that allow the correlationwith the finite element simulations.By means of Computed Tomography, a precise reconstruction of both bone and muscle of therat hindlimb geometry was obtained. The methodology proposed allows to obtain and validatecomputational simulations of skeletal muscle fatigue under different characteristics related tofiber types.63